Architecture and structural evolution of an early Little Ice Age terminal moraine at the surge‐type glacier Múlajökull, Iceland. Issue 9 (24th September 2015) - Benediktsson, Ívar Örn; Schomacker, Anders; Johnson, Mark D.; Geiger, Alessa J.; Ingólfsson, Ólafur; Guðmundsdóttir, Esther Ruth
Abstract The internal architecture and structural evolution of the Arnarfellsmúlar terminal moraine at Múlajökull, a surge‐type glacier in central Iceland, is described in order to demonstrate submarginal and proglacial glaciotectonic processes during glacier surging, as well as constraining the age of the maximum extent of the glacier. The moraine is 4–7 m high, 50–100 m wide, and composed of a highly deformed sequence of loess, peat, and tephra that is draped by till up to the crest. The internal architecture is dominated by steep, high‐amplitude overturned folds and thrusts in the crest zone but open, low‐amplitude folds on the distal slope. Section balancing suggests a basal detachment (décollement) depth of 1.4 m and a total horizontal shortening of around 59%. This implies that the glacier coupled to the foreland about 70 m up glacier from its terminal position to initiate the formation of the moraine. The structural evolution is polyphase in that the formation commenced with low‐amplitude open folding of the foreland, followed by overfolding and piggyback thrusting. Radiocarbon dating and analysis of tephra layers, along with historical references, indicate that the most likely time of moraine formation was between A.D. 1717 and 1760, which suggests that Múlajökull had its Little Ice Age maximum and most extensive surge earlier than many other surge‐type glaciers in Iceland.